QUALIDADE DO EFLUENTE DE PISCICULTURA TRATADO POR FILTROS BIOLÓGICOS (AERÓBIO E ANAERÓBIO) PARA SER USADO NA IRRIGAÇÃO - Manso, Rannaiany Teixeira; Cunha, Fernando Nobre; Teixeira, Marconi Batista; Alves, Daniely Karen Matias; Cabral Filho, Fernando Rodrigues (IRRIGA, 2022)
QUALITY OF EFFLUENT OF PISCICULTURE TREATED BY AEROBIC AND ANAEROBIC BIOLOGICAL FILTERS TO BE USED IN IRRIGATION RANNAIANY TEIXEIRA MANSO1; FERNANDO NOBRE CUNHA1; MARCONI BATISTA TEIXEIRA1; DANIELY KAREN MATIAS ALVES1 E FERNANDO RODRIGUES CABRAL FILHO1 1Departamento de Hidráulica e Irrigação, Instituto Federal Goiano – Campus Rio Verde, Rodovia Sul Goiana, Km 01, CEP: 75.901-170, Rio Verde – GO, rannaiany@gmail.com, fernandonobrecunha@hotmail.com, marconi.teixeira@ifgoiano.edu.br, daniely_karen@hotmail.com, fernandorcfilho@hotmail.com. 1 ABSTRACT Fish farming depends on environmental products and services for their sustainability, such as effluent and waste dilution capacity and availability of good quality water. The environmental problems related to the practice of this activity have to do with the water quality of effluents from fishponds that have organic matter, suspended solids and high concentrations of nutrients. Therefore, the objective of the present study was to analyze the quality of pisciculture effluents treated by two biological filters for release or use in agriculture. The experiment was conducted at the IFGoiano, Rio Verde campus, where two fish farming systems were built, with two different biological filters, the aerobic gravel filter (FB) and the anaerobic bamboo filter (FA), where collections were made at the exit of each one to verify the effluent quality for release and / or irrigation purposes. A completely randomized experimental design was used, in a 2×4 split-plot arrangement, and with three replications. The treatments consisted of four collection times, after the implementation of the experiment (60, 70, 80, and 90 DAI) and two filter types (anaerobic bamboo filter; and aerobic stone filter). The quality of the treated effluent was analyzed in the laboratories of Hydraulic and Irrigation; Sanitation and Environment; and Water and Effluents of the GFI-RV. The parameters evaluated were: electrical conductivity, total dissolved solids, pH, turbidity, alkalinity, chemical oxygen demand (COD), dissolved oxygen (DO), and biochemical oxygen demand (BOD). The parameters pH, total dissolve solids, turbidity, DO, and BOD were in accordance with the standards established by the CONAMA 357/05 for Class II waters (allowing use for irrigation of vegetables and fruit plants). Keywords: Aquaculture, water resources, reuse, release. MANSO, R. T.; CUNHA, F. N.; TEIXEIRA, M. B.; ALVES, D. K. M.; CABRAL FILHO, F. R. QUALIDADE DO EFLUENTE DE PISCICULTURA TRATADO POR FILTROS BIOLÓGICOS (AERÓBIO E ANAERÓBIO) PARA SER USADO NA IRRIGAÇÃO 2 RESUMO A piscicultura depende de produtos e serviços ambientais para a sua sustentabilidade, tais como capacidade de diluição de efluentes e resíduos e disponibilidade de água de boa qualidade. Os problemas ambientais relacionados com a prática desta atividade, tem a ver com a qualidade da água dos efluentes de viveiros de peixes que apresentam matéria orgânica, sólido em suspensão e altas concentrações de nutrientes. Desta forma, objetivou-se analisar a qualidade do efluente de piscicultura ao passar por dois diferentes filtros biológicos para fins de lançamentos ou aproveitamento na agricultura. O trabalho foi conduzido no IFGoinao - Campus Rio Verde, onde foram construídos dois sistemas de piscicultura, com dois diferentes filtros biológicos, sendo o filtro aeróbio de brita (FB) e o filtro anaeróbio de bambu (FA), onde se realizou coletas na saída de cada um para se verificar a qualidade do efluente para fins de lançamento e/ou irrigação. O delineamento experimental utilizado foi inteiramente casualizado, analisado em esquema de parcelas subdivididas 2 × 4, com três repetições. Os tratamentos são quatro épocas de coletas após a instalação (60, 70, 80 e 90 DAI) e dois tipos de filtros (filtro anaeróbio de bambu e filtro aeróbio de brita). Avaliou-se parâmetros físico-químicos: turbidez, pH, alcalinidade, condutividade elétrica, demanda química de oxigênio (DQO), demanda bioquímica de oxigênio (DBO), oxigênio dissolvido (OD) e Sólidos Dissolvidos Totais (SDT). Em geral, pode se concluir que os parâmetros pH, SDT, turbidez, OD e DBO se enquadraram na resolução CONAMA 357/05, para classe II (permitindo o uso para irrigação de hortaliças e plantas frutíferas). Palavras-chave: Aquicultura, recursos hídricos, reuso, lançamento.